Laryngopharyngeal reflux: clinical significance, modern approaches to diagnosis and treatment - I. V. Maev; J. V. Selskaya; D. N. Andreev; D. T. Dicheva; Z. N. Bogolepova; E. I. Kuznetsova (Медицинский совет, 2019)
Gastroesophageal reflux disease (GERD) is one of the most common pathologies in modern clinical practice. Laryngopharyngeal reflux (LPR) is considered to be an extraesophageal manifestation of GERD and is characterized by retrograde ingestion of gastric content into the larynx and pharynx, leading to recurrent otolaryngological symptoms. Classical manifestations of LPR are hoarseness, perspiration, dryness and feeling of lump in the throat, coughing. There is no «gold standard» for the diagnosis of LPR. At the same time, several instrumental methods are used in clinical practice to verify the diagnosis: laryngoscopy and EGDS are the most common, and in some cases - 24-hour pH-metry and impedancemetry. In the case of an established diagnosis of LPR, it is recommended to use a standard dosage of PPI twice a day for 3–6 months.